Changes in illicit, licit and stimulant designer drug use patterns in South-East Hungary between 2008 and 2015. (September 2017) - Árok, Zsófia; Csesztregi, Tamás; Sija, Éva; Varga, Tibor; Kereszty, Éva M.; Tóth, Réka Anita; Institóris, László
Highlights: Biological samples of 2976 suspected drug users were analyzed between 2008–15. Cannabis consumption decreased, the frequency of classical stimulants was constant. Stimulant designer drugs (SDDs) reached the highest prevalence in 2012–13. The percentage of multi-drug use was 30–43% until 2015 then increased to 52%. Illicit drug and SDD consumption corresponded to their seizure rate. Abstract: The aim of this work is to present the changes in classical illicit and licit drug, as well as stimulant designer drug (SDD) consumption of suspected drug users in South-East Hungary between 2008 and 2015. Urine and/or blood samples of 2976 subjects were analyzed for these groups of substances of which 1777 (59.7%) were tested positive. THC was the most frequent (32.2%) substance, followed by classical stimulants (amphetamine, metamphetamine, MDMA, cocain) (21.4%), SDDs (17.0%), benzodiazepines (15.5%), medical opiates (codeine without morphine, methadone, tramadol) (4.03%), and morphine with or without 6-acethyl-morphine (1.98%). The annual rate of cannabis consumption continuously decreased after 2010. The use of classical stimulants was constant, except for a significant increase in 2015. Benzodiazepine incidence increased and remained steady after 2011. Medical opiate and morphine frequency was variable. SDDs were found in the highest number in 2012–13, exceeding the frequency of classical stimulants. The most prevalent SDDs were as follows: 2010 – mephedrone, 2011 – 4-MEC, methylone, MDPV, 4-FMC, and 4-FA, and 2012–2015 – pentedrone. Beside pentedrone, 3-MMC, αPVP, αPHP, and 4-CMC were detected with a notable number in this period. Multi-drug use was found in 30–43% of suspects tested positive between 2008 and 2014, which elevated to 52% in 2015. The frequency of substances in the biological samples corresponded to their seizure rate. When SDDs were included on the NPS list, their frequency in biological samples and in seized materials slightly decreased or did not change. However, a marked decrease was observed following classification as illicit drugs.